Students’ Perception on the Use of U-dictionary to Support Vocabulary Retention - Halimathusadiah Halimathusadiah; Zuraida Zuraida (Linguistic, English Education and Art (LEEA) Journal, 2026)
The purpose of this study was to find out the students’ perception on the use of U-Dictionary toward the vocabulary ability. In research, a well-structured research design is essential. The results of this study indicate that students' perceptions of the use of U-Dictionary were generally positive. The majority of respondents stated that U-Dictionary is effective in helping their vocabulary ability, especially because of features. Contextual features such as example sentences and synonyms play an important role in vocabulary retention. Accessibility was the main reason for using U-Dictionary. The app's ability to be used in offline mode was considered a major advantage, especially for students with limited internet access. U-Dictionary has a greater impact on their vocabulary ability and reading comprehension, but is less significant in developing overall speaking and writing skills. Preferably students can maximize to utilizing U-Dictionary not only as an instant translation tool, but also actively utilizing supporting features. Keywords: Students, Perception, U-Dictionary, Vocabulary